Text-message reminders in colorectal cancer screening: a non-clinical randomised controlled trial. (November 2016) - Hirst, Yasemin; Skrobanski, Hanna; Kerrison, Robert; Kobayashi, Lindsay C; Counsell, Nicholas; Djedovic, Natasha; Ruwende, Josephine; Stewart, Mark; von Wagner, Christian
Abstract: Background: In England, adults aged 60–74 years are eligible for colorectal cancer screening using a guaiac faecal occult blood test (gFOBt) kit. However, uptake of the gFOBt kit in London has been consistently below the national target. We investigated the effectiveness of a text-message reminder to improve uptake of the test kit in London. Methods: General practices in six Clinical Commissioning Groups (CCGs) in London were invited to take part in this randomised controlled trial. Between Jan 18 and March 14, 2016, screening-eligible adults were randomised (1:1, using a pseudorandom number generator) to the control group (gFOBT screening pathway in the English Bowel Cancer Screening Programme [usual care]) or intervention group (usual care plus a text-message reminder). Individuals in the intervention group who had not returned their screening kit were sent a reminder text-message on the eighth week of an 18 week gFOBt screening episode. The primary outcome was the total proportion of individuals returning the kit by 18 weeks, which was determined with intention-to-treat analysis. Ethics approval was given by the East Midlands National Research Ethics Service (15/EM/0159) and the Confidentiality Advisory Group (15/CAG/0156). This trial is registered with ISRCTN, number ISRCTN70904476. Findings: 141 (48%) of 295 general practices participated, and 8269 individuals were randomised (4135 usual care, 4134 intervention). Only 49% of individuals in both groups had registered a mobile number with their practice (n=4089). In the intervention group, 1393 individuals with a registered mobile had not returned their test kit within 8 weeks; reminder text-messages were successfully delivered to 1026 individuals (74%), of whom 189 (18%) subsequently took part in screening. Intention-to-treat analysis showed that uptake was 40% (1648 of 4135) in the control and 41% (1674 of 4134) in the intervention group (odds ratio 1·04, 95% CI 0·95–1·13; p=0·43). Pre-planned exploratory subgroup analyses showed no effect on uptake by sex, index of deprivation, age, or CCG. However, a 6 percentage point difference in uptake was seen among individuals receiving an invitation for the first time (control 35% [282/809] vs intervention 41% [297/733]) (odds ratio 1·31, 95% CI 1·00–1·71; p=0·03). Interpretation: Text-message reminders did not significantly increase the number of adequately screened individuals in London. Future research might however investigate the potential efficacy of text-messages among individuals invited for screening for the first time. Funding: London North West Healthcare NHS Trust.